Advertising campaign planning: developing an advertising - based marketing plan - Avery, Jim (Chicago: The Copy Worksjop, 1993)
Contents: things to know before you start: planning point 1. target audience of this book. planning point 2. working procedures. planning point 3. writing style. planning point 4. advertising campaign outline. the marketing planning document: 1. situation analysis. 2. research. 3. problems and oportunities. 4. marketing objective. 5. budget. 6. marketing strategy. 7. advertising creative. 8. advertising media. 9. sales promotion. 10. evaluation. 11. test marketing.
Keywords: Publicidad - Propaganda